The Applicability of Using Automation in Construction in Iraq - Dakhil, Ammar Jasim; Naji, Zaher Mohamed; Alsalih, Osama Salim Abdulkareem (Basrah Journal for Engineering Sciences, 2021)
Several governments around the world announced new strategies regarding their construction industry. These strategies focus on reducing construction projects’ time, cost and improving their impact on the environment. To achieving these goals within the proposed time scale, these authorities advise their stakeholders to start to implement different methods in project delivery such as Building Information Modeling (BIM), Integrated Project Delivery (IPD), Geographic Information System (GIS), and many more. All these new technologies and methods will reduce human errors in the project lifecycle which will lead to reducing project waste. In addition, this will pave the road to automation in construction. Automation will help to mitigate the huge number of clashes and mistakes. Iraq an oil-depended country suffering from economic crises due to the considerable reduction in oil prices. This struggle must enforce the government to use this opportunity to solve current project problems such as project delays and budgets overrun and rethink how to reduce construction project time and cost. However, the applicability and understanding of these new methods and technologies need to be explored first among the Iraqi construction industry. This paper will investigate the understanding of automation in construction among different disciplines working with different experiences in the Iraq construction industry. The method of survey was used to sightsee their view regarding automation in construction understanding, benefits, and the challenges. The results reveal that there a positive view in terms of understating the meaning of automation in construction. In addition, several benefits are identified as the most effective gains if these new methods are implemented. Furthermore, more than a few challenges also have been acknowledged that need to be considered to increase the successfulness of implementing automation in construction.